2018
DOI: 10.1007/s00018-018-2911-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-124-3p is a chronic regulator of gene expression after brain injury

Abstract: Traumatic brain injury (TBI) initiates molecular and cellular pathologies that underlie post-injury morbidities, including hippocampus-related memory decline and epileptogenesis. Non-coding small RNAs are master regulators of gene expression with the potential to affect multiple molecular pathways. To evaluate whether hippocampal gene expression networks are chronically regulated by microRNAs after TBI, we sampled the dentate gyrus of rats with severe TBI induced by lateral fluid-percussion injury 3 months ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 137 publications
1
39
0
Order By: Relevance
“…Neuroinflammatory signaling is in part controlled by miR‐146a, and overexpression of miR‐146a following status epilepticus potently suppresses spontaneous recurrent seizures in mice . In addition, reduced levels of miR‐124 have been proposed to promote epileptogenesis through inflammatory and epigenetic targets in models of status epilepticus and traumatic brain injury . Thus, miRNAs also provide direct targets for antiepileptogenesis and disease‐modifying therapy development.…”
Section: Why Micrornas As Molecular Biomarkers Of Epilepsy?mentioning
confidence: 99%
“…Neuroinflammatory signaling is in part controlled by miR‐146a, and overexpression of miR‐146a following status epilepticus potently suppresses spontaneous recurrent seizures in mice . In addition, reduced levels of miR‐124 have been proposed to promote epileptogenesis through inflammatory and epigenetic targets in models of status epilepticus and traumatic brain injury . Thus, miRNAs also provide direct targets for antiepileptogenesis and disease‐modifying therapy development.…”
Section: Why Micrornas As Molecular Biomarkers Of Epilepsy?mentioning
confidence: 99%
“…miR-124-3p drive cells towards neuronal identity [35,36], and regulates gene expression by promoting neuron-specific splicing [37]. Our previous study on post-TBI downregulation of miR-124-3p in the dentate gyrus suggested a link between miR-124-3p and post-injury hippocampal pathologies such as epileptogenesis and memory decline [19]. To explore the role of miR-124-3p in the progression of cortical damage, we investigated the post-TBI expression pattern of miR-124-3p in the perilesional cortex in experimental and human TBI.…”
mentioning
confidence: 94%
“…miRNA-based treatments show potential as disease-modifying network therapies after experimental TBI [9][10][11].Despite an increasing number of reports describing alterations in the regulation of miRNAs after TBI, our understanding of the regulation of the miRNome and its cellular localization after TBI is still in its infancy [12,13]. TBI regulates brain miRNA expression acutely [14][15][16][17], and some miRNAs remain regulated chronically-months to years after TBI [18,19]. Dysregulated miRNA levels are reported in the cortex [9,14,[20][21][22], hippocampus [15,16,18,19,[23][24][25][26][27], and plasma [28][29][30].…”
mentioning
confidence: 99%
See 2 more Smart Citations